Smoking Cessation Intervention for severe Mental Ill Health Trial (SCIMITAR): a pilot randomised control trial of the clinical effectiveness and cost-effectiveness of a bespoke smoking cessation service - Emily Peckham (Health Technology Assessment, 2015)
Background: There is a high prevalence of smoking among people who experience severe mental ill health (SMI). Helping people with disorders such as bipolar illness and schizophrenia to quit smoking would help improve their health, increase longevity and also reduce health inequalities. Around half of people with SMI who smoke express an interest in cutting down or quitting smoking. There is limited evidence that smoking cessation can be achieved for people with SMI. Those with SMI rarely access routine NHS smoking cessation services. This suggests the need to develop and evaluate a behavioural support and medication package tailored to the needs of people with SMI. Objective: The objective in this project was to conduct a pilot trial to establish acceptability of the intervention and to ensure the feasibility of recruitment, randomisation and follow-up. We also sought preliminary estimates of effect size in order to design a fully powered trial of clinical effectiveness and cost-effectiveness. The pilot should inform a fully powered trial to compare the clinical effectiveness and cost-effectiveness of a bespoke smoking cessation (BSC) intervention with usual general practitioner (GP) care for people with SMI. Design: A pilot pragmatic two-arm individually randomised controlled trial (RCT). Simple randomisation was used following a computer-generated random number sequence. Participants and practitioners were not blinded to allocation. Setting: Primary care and secondary care mental health services in England. Participants: Smokers aged > 18 years with a severe mental illness who would like to cut down or quit smoking. Interventions: A BSC intervention delivered by mental health specialists trained to deliver evidence-supported smoking cessation interventions compared with usual GP care. Main outcome measures: The primary outcome was carbon monoxide-verified smoking cessation at 12 months. Smoking-related secondary outcomes were reduction of number of cigarettes smoked, Fagerstrom test of nicotine dependence and motivation to quit (MTQ). Other secondary outcomes were Patient Health Questionnaire-9 items and Short Form Questionnaire-12 items to assess whether there were improvements or deterioration in mental health and quality of life. We also measured body mass index to assess whether or not smoking cessation was associated with weight gain. These were measured at 1, 6 and 12 months post randomisation. Results: The trial recruited 97 people aged 19–73 years who smoked between 5 and 60 cigarettes per day (mean 25 cigarettes). Participants were recruited from four mental health trusts and 45 GP surgeries. Forty-six people were randomised to the BSC intervention and 51 people were randomised to usual GP care. The odds of quitting at 12 months was higher in the BSC intervention (36% vs. 23%) but did not reach statistical significance (odds ratio 2.9; 95% confidence interval 0.8% to 10.5%). At 3 and 6 months there was no evidence of difference in self-reported smoking cessation. There was a non-significant reduction in the number of cigarettes smoked and nicotine dependence. MTQ and number of quit attempts all increased in the BSC group compared with usual care. There was no difference in terms of quality of life at any time point, but there was evidence of an increase in depression scores at 12 months for the BSC group. There were no serious adverse events thought likely to be related to the trial interventions. The pilot economic analysis demonstrated that it was feasible to carry out a full economic analysis. Conclusions: It was possible to recruit people with SMI from primary and secondary care to a trial of a smoking cessation intervention based around behavioural support and medication. The overall direction of effect was a positive trend in relation to biochemically verified smoking cessation and it was feasible to obtain follow-up in a substantial proportion of participants. A definitive trial of a bespoke cessation intervention has been prioritised by the National Institute for Health Research (NIHR) and the SCIMITAR pilot trial forms a template for a fully powered RCT to examine clinical effectiveness and cost-effectiveness. Trial registration: Current Controlled Trials ISRCTN79497236. Funding: This project was funded by the NIHR Health Technology Assessment programme and will be published in full in Health Technology Assessment, Vol. 19, No. 25. See the NIHR Journals Library website for further project information.